A karyomorphological study on the genus Muscari Mill. growing in Kahramanmaraş (Turkey) - Kayıran, Serpil Demirci; Özhatay, Fatma Neriman (My University, 2017)
The karyotypes and idiograms of nine Muscari Mill. species from 21 populations distributed in Kahramanmaraş province, southern Turkey, were examined: M. armeniacum Leichtlin ex Baker 2n = 18 (diploid); M. aucheri (Boiss.) Baker 2n = 18 (diploid); M. anatolicum Cowley & Özhatay 2n = 27 (triploid); M. neglectum Guss. 2n = 18 (diploid), 36 (tetraploid), 54 (hexaploid); M. parviflorum Desf. 2n = 36 (tetraploid); M. babachii Eker & Koyuncu 2n = 18 (diploid); M. comosum Miller 2n = 18 (diploid); M. tenuiflorum Tausch 2n = 18 (diploid); and M. azureum Fenzl 2n = 18 (diploid). M. anatolicum is an endemic species to Turkey and the 2n = 27 triploid population for this species is recorded for the first time. Idiograms and karyotypes of the species were obtained by the use of Cameram software.
Keywords: Biyoloji